2012
DOI: 10.1371/journal.pone.0035301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dual Task on Postural Control in Dyslexic Children

Abstract: Several studies have examined postural control in dyslexic children; however, their results were inconclusive. This study investigated the effect of a dual task on postural stability in dyslexic children. Eighteen dyslexic children (mean age 10.3±1.2 years) were compared with eighteen non-dyslexic children of similar age. Postural stability was recorded with a platform (TechnoConcept®) while the child, in separate sessions, made reflex horizontal and vertical saccades of 10° of amplitude, and read a text silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 60 publications
10
29
0
1
Order By: Relevance
“…Moreover, in the condition without vibration, the attentional performance of dyslexics was significantly impaired compared to that of the non-dyslexic group of children. Our group [13] also reported that children with dyslexia were significantly more unstable than non-dyslexic children when reading text silently. Taken together, all these findings suggest that the cerebellum, which is responsible for the integration of proprioceptive inputs during balance, could be impaired in the dyslexic population.…”
Section: Introductionsupporting
confidence: 51%
“…Moreover, in the condition without vibration, the attentional performance of dyslexics was significantly impaired compared to that of the non-dyslexic group of children. Our group [13] also reported that children with dyslexia were significantly more unstable than non-dyslexic children when reading text silently. Taken together, all these findings suggest that the cerebellum, which is responsible for the integration of proprioceptive inputs during balance, could be impaired in the dyslexic population.…”
Section: Introductionsupporting
confidence: 51%
“…It is possible that this difference is due to the fact that the study examined older dyslexics with postural characteristics closer to those of adults (age range of 14–17 years). Other researchers, in examining the effect of a dual task on postural control in dyslexic children, studied 18 dyslexic children (mean age 10.3 ± 1.2 years) who were compared with 18 nondyslexic children of similar ages, seemed to have confirmed that dyslexic children are significantly more unstable during the reading task compared with a simple reflex horizontal and vertical saccades task 113. This postural instability could indicate that such children lack the integration of multiple sensorimotor inputs.…”
Section: Visual Therapy For Dyslexiamentioning
confidence: 92%
“…Moreover, significant differences on postural control performance between dyslexic children and age- and gender-matched controls were also reported in previous studies involving dual task. These studies clearly demonstrated that the postural control of dyslexic children was highly impaired by addition of a second task that increases attentional demands [57]. …”
Section: Introductionmentioning
confidence: 99%